The Platelet/Monocyte Ratio Before Treatment Predicts Prognosis in Solid Childhood Cancers - Terzi, Özlem; Bayram, Cengiz; Ayçiçek, Ali; Uysalol, Ezgi; Nur Baş, Cennet; Solgun, Hüseyin Avni; Tahtakesen, Tuba; Arslantaş, Esra; Tekgündüz, Sibel (Medical Laboratory Technology Journal, 2022)
The prognostic value of thrombocytosis and inflammatory biomarkers in adult cancer patients has been the subject of many studies. This study investigated the role of platelet count and other inflammatory biomarkers in the prognosis of solid childhood tumours. The data of 176 pediatric patients diagnosed with solid tumours were evaluated retrospectively; 150 patients still under follow-up were included in the study. We examined the relationship between platelet count, platelet/neutrophil ratio (PNR), platelet/lymphocyte ratio (PLR) and platelet/monocyte ratio (PMR) at the time of diagnosis on survival. The mean age of diagnosis was 7.91 ± 5.75 years, and 60.7% were male. The mean platelet count of the patients was 424.326 ± 167197.32. The median (range) follow-up was 13 (1-68) months. Relapse was seen in 18% of the patients, and 9.3% died. The relationship between PMR and overall survival (OS) and event-free survival times (EFS) was statistically significant (p=0.002 and p=0.016, respectively). However, no statistically significant association was found for PLR or PNR. Overall survival and EFS were significantly poorer in this cohort in patients with high pretreatment PMR.